The impact of constrained monetary policy on fiscal multipliers on output and inflation - Tilman Bletzinger; Magdalena Lalik (European Central Bank (ECB), 2017)
This paper uses two established DSGE models (QUEST III and Smets-Wouters) to assess the impact of fiscal spending cuts on output and, in particular, also on inflation in the euro area under alternative settings for monetary policy. We compare four different settings of constrained monetary policy, taking into account alternative agents' expectations about future monetary policy. We illustrate that those expectations are even more important for the size of the fiscal multipliers than the difference between exogenously versus endogenously modelled constraints. We confirm the well-known finding that fiscal multipliers exhibit an over-proportional reaction when monetary policy is constrained. The novelty of our results is that this over-proportionality is stronger for the fiscal multiplier on inflation than on output. We relate this finding to the structural parameters of the models by means of a Global Sensitivity Analysis.
Keywords: E31; E43; E52; E62; E63; 330; constrained monetary policy; fiscal multipliers; zero lower bound